Drei Prioritäten für die neue Bundesregierung - Daniel Gros (Wirtschaftsdienst, 2025)
– The new German government will have three fundamental policy issues to wrestle with: the war in Ukraine and European security, the future of global trade, and structural issues that hold back growth. Ukraine: If U.S. support wanes, Europe must stand ready. Trade: Trump's tariffs offer opportunities. Structural issues: Germany lags in high-tech sectors and needs long-term structural reforms.
Keywords: F21; F60; H11; H50; H60; 330; Wirtschaftspolitik; Europapolitik; Deutschland; Wirtschaftspolitik; Europapolitik; Deutschland